ANALISA PERHITUNGAN DINDING PENAHAN TANAH PEKERJAAN PENGENDALIAN BANJIR SUNGAI KEDUKAN KECAMATAN GANDUS KOTA PALEMBANG - Muhammad Prasetian Idha; Hidayat, Ahmad (Politeknik Negeri Sriwijaya, 2025)
A retaining wall functions to resist soil mass and prevent landslides caused by rainfall, soil weight, or other external loads. Currently, retaining wall structures are widely applied in civil engineering projects, although their use has been known since ancient times. This study examines safety factors including soil bearing capacity, shear force, and stability against overturning. The objective is to analyze the causes of retaining wall failure and to design the reconstruction of the collapsed section. The analysis results indicate that the existing retaining wall is not stable against shear, with a value of 1.28 < 1.5. Therefore, a redesign was carried out using a gravity retaining wall with a vertical back face, which is suitable for high walls. From this design, shear stability of 1.67 > 1.5 and overturning stability of 3.9 > 1.5 were obtained, thus declared safe.